The Emergence of Traditional Music - Botirov Maqsadjon Ibrakhimovich (International Journal on Integrated Education, 2021)
this article contains information about the legacy of Uzbek composers and musicians. Information about the great contribution of allomals to Uzbek music has been provided. The services of our zabardast hafizas in the singing section have been highlighted.